Response Format, Not Semantic Activation, Influences the Failed Retrieval Effect - Tanaka, Saeko; Miyatani, Makoto; Iwaki, Nobuyoshi (Frontiers in Psychology, 2019)
In educational settings, tests are mainly used to measure the extent to which learners’ knowledge and skill have been acquired. However, the act of taking a test also promotes learning itself. In particular, making errors on tests (i.e., searching for erroneous information) promotes learning. This is called the “failed retrieval effect” (FRE) and has been the subject of considerable study. Previous research shows that enhanced learning does not occur if feedback correcting an error is delayed. This is attributed to the relative absence of activated information. In this study, we manipulated both the amount of information to be retrieved prior to learning and the delay time until feedback is given to investigate their effects on learning. As a result, even when multiple incorrect answers were given to increase the degree of semantic activation, learning was not promoted beyond that found with traditional procedures that rely on only one incorrect response. The timing of feedback (immediate, short-delay, long-delay) also did not impact FRE. However, the manipulation of response format for erroneous information resulted in degraded performance when responses were typed and feedback was delayed. Based on this result, we suggested that the failed retrieval effect was not affected by semantic activation at the time of retrieval but was affected by response format. Moreover, the processing necessary for typing may affect FRE under the delayed feedback condition.